L-Cysteine Provides Neuroprotection of Hypoxia-Ischemia Injury in Neonatal Mice via a PI3K/Akt-Dependent Mechanism - Li T; Li J; Li T; Zhao Y; Ke H; Wang S; Liu D; Wang Z (Dove Medical Press, 2021)
Tingting Li,1,* Jiangbing Li,1,2,* Tong Li,3,* Yijing Zhao,1 Hongfei Ke,1 Shuanglian Wang,1 Dexiang Liu,4 Zhen Wang1 1Department of Physiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 2Department of Cardiology, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Neurosurgery Surgery, Qingdao Municipal Hospital, Shandong Province, People’s Republic of China; 4Department of Medical Psychology and Ethics, School of Basic Medicine Sciences, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dexiang LiuDepartment of Medical Psychology and Ethics, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, 250012, People’s Republic of ChinaEmail liudexiang@sdu.edu.cnZhen WangDepartment of Physiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, 44 Wenhua Xi Road, Jinan, Shandong, 250012, People’s Republic of ChinaEmail wangzhen@sdu.edu.cnBackground: Previous work within our laboratory has revealed that hydrogen sulfide (H2S) can serve as neuroprotectant against brain damage caused by hypoxia-ischemia (HI) exposure in neonatal mice. After HI insult, activation of the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) signaling pathway has been shown to be implicated in neuro-restoration processes. The goal of the current study was to determine whether the neuroprotective effects of H2S were mediated by the PI3K/Akt signaling pathway.Methods: The mouse HI model was built at postnatal day 7 (P7), and the effects of L-Cysteine treatment on acute brain damage (72 h post-HI) and long-term neurological responses (28 days post-HI) were evaluated. Nissl staining and Transmission electron microscopy were used to evaluate the neuronal loss and apoptosis. Immunofluorescence imaging and dihydroethidium staining were utilized to determine glial cell activation and ROS content, respectively.Results: Quantitative results revealed that L-Cysteine treatment significantly prevented the acute effects of HI on apoptosis, glial cell activation and oxidative injury as well as the long-term effects upon memory impairment in neonatal mice. This protective effect of L-Cysteine was found to be associated with the phosphorylation of Akt and phosphatase and a tensin homolog deletion on chromosome 10 (PTEN). Following treatment with the PI3K inhibitor, LY294002, the neuroprotective effects of L-Cysteine were attenuated.Conclusion: PTEN/PI3K/Akt signaling was involved in mediating the neuroprotective effects of exogenous H2S against HI exposure in neonatal mice.Keywords: Akt, H2S, hypoxia-ischemia, neuroinflammation